Change models and strategies in the context of managing curriculum change: A case study of managing curriculum Year Four History Curriculum in the district of Kuala Selangor, Malaysia - Paramasivam, Thangamalar (Journal of Research, Policy & Practice of Teachers and Teacher Education, 2018)
This article is based on a case study of the management of curriculum change in primary schools. This was done by analyzing the management of curriculum change brought about by the introduction the History curriculum for the Year Four Primary Schools Standard-Based Curriculum. This instrumental case study employed a descriptive- interpretative approach grounded in the qualitative research tradition. Data was collected through analysis of documents, in-depth semi-structured interviews and the direct observations of teaching and learning of History lessons. It was located within the context of eight selected schools. A total of twenty eight participants (8 History teachers, 8 senior curriculum assistants, 8 headmasters, 1 National Trainer and 3 officers from Curriculum Development Division, State Education Department and District Education were interviewed. The process and procedures in managing curriculum change were analyzed in the context of characteristic of Havelock’s model, Schon’s models and Bennis, Benne and Chin’s innovation strategy. The findings showed that the central agency did predominantly use Havelock’s (1971) Research, Development & Diffusion model coupled with Schon’s (1971) Centre Periphery Model and Bennis et al.(1969) power-coercive strategy. However, the overall analysis showed that empirical rational and normative re-educative strategies were less practiced in managing the curriculum change.